Latching control of a raft-type wave energy converter with a hydraulic power take-off system. (15th September 2021) - Liu, Changhai; Hu, Min; Zhao, Zhixue; Zeng, Yishan; Gao, Wenzhi; Chen, Jian; Yan, Hao; Zhang, Junhui; Yang, Qingjun; Bao, Gang; Chen, Suxin; Wei, Daozhu; et al.
Abstract: The raft-type wave energy converter (WEC), consisting of several hinged rafts and hydraulic power take-off (PTO) systems, captures wave power in a line absorber manner, whose scattered and radiated wave pattern is different from that of a point absorber. This paper focuses on the latching control of a raft-type WEC consisting of two rafts and a hydraulic PTO system. To reduce the complexity of finding the optimal latching duration, the hydraulic PTO system is modelled as a Coulomb damping and the optimal latching control law is derived from a Coulomb damping-based model using the optimal control theory. The effectiveness of latching control on improving power capture ability of the raft-type WEC with a hydraulic PTO system and the benefit introduced by latching control in terms of power improvement are investigated. Results show that the optimal latching control law derived from the Coulomb damping-based model can effectively improve the power capture ability of the raft-type WEC with a hydraulic PTO system. The benefit due to latching control can reach a peak value of 3.04, which is 2 times that introduced by load control. Moreover, latching control can further benefit the raft-type WEC where load control has been performed. Highlights: Coulomb damping characteristics of the hydraulic PTO system is considered. Determination of the optimal latching duration is specified and studied. Effectiveness of latching control on a raft-type WEC with a hydraulic PTO is studied. Benefit due to latching control in terms of power improvement is investigated. Latching control can further benefit the raft-type WEC where load control has been performed.